Minimal Cognitive Impairment in UK HIV-Positive Men Who Have Sex With Men: Effect of Case Definitions and Comparison With the General Population and HIV-Negative Men - McDonnell, Jeffrey (JAIDS Journal of Acquired Immune Deficiency Syndromes, 2014)
BACKGROUND: To determine the prevalence of neurocognitive impairment (NCI) in UK HIV-positive and HIV-negative men who have sex with men (MSM). METHODS: HIV-positive and HIV-negative participants were recruited to a cross-sectional study from 2 London clinics and completed computer-assisted neuropsychological tests and questionnaires of depression, anxiety, and activities of daily living. Published definitions of HIV-associated neurocognitive disorders (HAND) and global deficit scores were used. Age- and education-adjusted neuropsychological test scores were directly compared with reference population data. RESULTS: A total of 248 HIV-positive and 45 HIV-negative MSM participated. In the HIV-positive group, median time since diagnosis was 9.4 years, median CD4(+) count was 550 cells per cubic millimeter, and 88% were on antiretroviral therapy. Prevalence of HAND was 21.0% in HIV-positive MSM (13.7% asymptomatic neurocognitive impairment, 6.5% mild neurocognitive disorder, and 0.8% HIV-associated dementia). Using a global deficit score threshold of 0.5, the prevalence of NCI was 31.5% (when averaged over 5 neuropsychological domains) and 40.3% (over 10 neuropsychological test scores). These results were not significantly different from the HIV-negative study sample. No consistent pattern of impairment was seen in HIV-positive patients relative to general male population data (n = 380). CONCLUSIONS: We found a prevalence of HAND and degree of impairment on neuropsychological testing of HIV-positive MSM that could represent a normal population distribution. These findings suggest that NCI may be overestimated in HIV-positive MSM, and that the attribution of NCI to HIV infection implied by the term HAND requires revision.